Homosexuality: a femme perspective in sexual relationship - Ab Aziz, Alice Nurizza; Abdul Rahman, Abdul Razak; Wan Jaafar, Wan Munira; Shahrimin Adam Assim, Mohd Ibrani (2018)
A fast-stead development of any countries of variables projects, high-rises souring the sky, would very much rooted down to its socio-cultural institutions and manpower development infrastructure capacity in parallel to the physical development components. However, in reality, socio-cultural and manpower institutions of most countries are not in reality, in parallel to its fast-stead development of such super-mega-development. The break-down of socio-cultural institutions related to various multiples social ills and issues spreading uncontrolled like a virus beyond managed and monitored becoming a factor of synonym within the society and the community. Social ills that need to be brought to serious attentions and arrested are the abnormal sexual relationship activities which are usually not easily observed but have been absorbed un-aware within the social frameworks that would despoil the social and religious institutions. This study focusses on homosexual behavior amongst women between Pengkid/Butch and Femme also known as lesbianism.This study concentrates on venturing and evaluating Femme perspective on interpersonal relationship with Pengkid/Butch. A semi-structured interview has been conducted on 10 Malay respondents in and around Kuala Lumpur and Selangor. The findings resulted in establishing the levels of the interpersonal relationship goes and its nature of activities in order to achieve an understanding on this group and mitigation approach that suit to this kind of situations. The findings of this study leads to new understanding on the behavior from the Femme as well as the duty and responsibility of community and affected Authorities and institutions to intervene these issues holistically